2014
DOI: 10.1177/1077546314555424
|View full text |Cite
|
Sign up to set email alerts
|

Iterative learning control for discrete-time switched systems with attenuation factor

Abstract: In order to decrease the effects of measurement noise on the trajectory tracking control of discrete-time switched systems, this paper proposes a discrete iterative learning control algorithm with an attenuation factor. The proposed algorithm adds a learning gain attenuated along the iteration horizon into measurement errors interfered by measurement noise for modifying the control rules of switched systems, in order to decay measurement noise as iterations increase. The convergence of each subsystem is proven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Pre-and post-multiplying both sides of (47) by diag{P i , Q i , P i , P i , Q i } and substituting (11) into (47) yield (37). It comes from (38), (41) and (42) that the condition (27) holds. Thus by Theorem 2, we can conclude that the system (10) is exponentially stable under the switching signal σ(t).…”
Section: Design Of Iterative Learning Controllermentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-and post-multiplying both sides of (47) by diag{P i , Q i , P i , P i , Q i } and substituting (11) into (47) yield (37). It comes from (38), (41) and (42) that the condition (27) holds. Thus by Theorem 2, we can conclude that the system (10) is exponentially stable under the switching signal σ(t).…”
Section: Design Of Iterative Learning Controllermentioning
confidence: 99%
“…A highorder ILC scheme for non-linear systems with parametric uncertainties was proposed in [26]. To decrease the effects of measurement noise on the trajectory tracking control of discretetime switched systems, an ILC algorithm with an attenuation factor was proposed in [27]. Besides, ILC method was also applied to the switched systems [12,28].…”
Section: Introductionmentioning
confidence: 99%
“…However, the method in [23] uses integral and fractional derivative, which makes the design of iterative learning controller complicated. In order to reduce the effect of measurement noise on the tracking accuracy of the system, the iterative learning control algorithm based on the attenuation of the learning gain along the iteration axis is proposed in [24], [25], which effectively suppresses the non-repeated measurement noise. Although the two algorithms retain the advantage of simpleness of the iterative learning controller, none of them can adjust the size of the learning gain based on the tracking error.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, some ILC strategies have been proposed by Bu et al (2013a, 2013b, 2013c), Yang (2015) and Cao and Sum (2014). Furthermore, an improved ILC scheme with attenuation factor has been addressed by Cao and Sum (2014). Reviewing the above studies, we found that most focus on analysing convergence or stability by employing the λ -norm theory and the lifted-system theory.…”
Section: Introductionmentioning
confidence: 99%